A non-invasive SiC MOSFET Junction temperature estimation method based on the transient light Emission from the intrinsic body diode. (November 2020) - Susinni, G.; Rizzo, S.A.; Iannuzzo, F.; Raciti, A.
Abstract: A non-invasive temperature sensing method for high-voltage SiC MOSFET chips based on the measurement of light emission during reverse conduction is proposed. The method is based on a compact sensing circuit that can be easily embedded in the package, allowing online temperature estimation. The effectiveness of the circuit has been confirmed by the analysis of a commercial SiC power module. The proposed temperature sensing strategy is fast, inexpensive, accurate, and non-invasive.